An audit of adherence to anti-tnf therapy in patients with inflammatory bowel disease. (13th March 2011) - Duncan, J; Sastrillo, M; Baker, J; Younge, L; Anderson, S; Lindsay, J; Sanderson, J; Irving, P
Abstract : Introduction: Poor adherence is associated with worse outcomes and healthcare costs. Anti-TNF therapy is increasingly used in IBD management. There are 2 anti-TNF agents available to treat IBD in the UK: Adalimumab (ADA), self-administered at home and Infliximab (IFX), administered by a healthcare professional in hospital. Accordingly potential barriers to adherence vary between the two drugs though little is known about this. Aim: to assess adherence to ADA and IFX in patients at two IBD tertiary referral centres; adherence to other IBD medication; and reasons for poor adherence. Methods: We reviewed adherence to anti-TNF therapy over the preceding 12 months by recording postponement of, or failure to attend, scheduled IFX infusions along with the frequency of, and reasons for, missed infusions. In patients self-administering ADA we assessed adherence using the Medication Adherence Report Scale (MARS).1 Additionally we recorded reasons for missed or delayed injections. Missed/postponed doses for medical reasons (eg, infections) were not counted as failure to adhere. Adherence to (MARS), and reasons for non-adherence were also recorded for 5-ASA and immunomodulators. Results: 106 patients were included (82 IFX, 24 ADA), 55 males. The median (range) age was 32 years (17–59). Median time on treatment was 17 months (1–110). There was no difference in the proportion of patients who failed to adhere to anti-TNF therapy completely (ADA 5/24 patients (21%): IFX 19/82 (23%), p=0.79). Over the preceding year, 5 IFX patients missed infusions on 8 occasions. 14 patients postponed a total of 32 infusions. Of those who failed to adhere to their scheduled infusions: 16 cited inconvenience and 1 forgot. The median MARS score in the ADA group was 25 (range 22–25). 3 people occasionally missed doses; 2 forgot and 1 cited inconvenience. 4 people delayed doses, most of whom forgot, although one cited the route of administration. 49 patients were on thiopurines, 8 methotrexate. 35% incompletely adhered to medication. The median MARS score was 25 (range 18–25). The most common reason for non-adherence was forgetting to take medication.8/18 patients on 5-ASA admitted to poor adherence. The median MARS score was 25 (range 15–25). Poor adherence was most commonly related to forgetting to take medication. Conclusion: Adherence to anti-TNF therapy is generally good. While the challenges to adherence are different for the two drugs, overall adherence is similar for IFX and ADA.